Why are Americans so divided on refugee policy? - MADAN, Shilpa (Institutional Knowledge at Singapore Management University, 2019)
The U.S. will resettle the lowest number of refugees in fiscal year 2019 since the Refugee Act was passed in 1980. After taking office, President Donald Trump reduced the admission limit from 110,000 in 2017 to 45,000 in 2018, and to 30,000 in 2019. The reduction is not a result of fewer refugees seeking resettlement. On the contrary, the number of people seeking resettlement is on the rise.